Unequal competition as an impediment to personal development: A review of the relative age effect in sport - Musch, J.M; Grondin, S. (Developmental Review, 2001)
Children born shortly before the cutoff date for age grouping in youth sport programs suffer from being promoted to higher age groups earlier than their later-born peers. Skewed birthdate distributions among participants in youth sport and professional sport leagues have been interpreted as the result of this disadvantage. A growing body of research shows that this Relative Age Effect in sport is a worldwide phenomenon and that it exists in many, but not all, competitive sports. Both physical and psychological mechanisms that may be responsible for the effect are identified. Negative consequences on personal development and possible remedies to the problem are discussed. Finally, desirable and necessary directions for future research are formulated.